SAT0095 REAL LIFE SEVERE INFECTIONS IN PATIENTS WITH RHEUMATOID ARTHRITIS ON TREATMENT WITH BIOLOGICAL THERAPY AND JAKI. (2nd June 2020) - Vega, L.; Calvo, I.; Ibarguengoitia, O.; Blanco, J. M.; Montero, D.; García, C.; Ruiz, M. E.; Inchaurbe, A. R.; Torre, I.; Perez, C. E.; Fernandez, O.; Cuande, E.; et al.
Abstract : Background: Infections are one of the main complications among patients with rheumatoid arthritis (RA) with immunosuppressive treatment. The differences between treatments and the influence of other factors is unclear. Objectives: To evaluate the frequency and factors associated with serious infections in patients with RA treated with biological therapy (BT) and JAKi and the differences between treatments. Methods: Descriptive and retrospective study (January 2015-December 2019) of patients with RA treated with BT (TNFi, non-TNFi) and JAKi (tofacitinib, bariticinib) in a single center. Severe infection was considered a life-threatening infection or one that required hospitalization and intravenous treatment. Epidemiological variables, clinical characteristics, Charlson comorbidity index, type of BT or JAKi and concomitant treatment were collected. For the analysis frequencies and percentages are used in qualitative variables, and mean ± SD in the quantitative ones. Statistical analysis was performed with IBM SPSS v 23. Results: We registered 246 patients (85% women) mean aged 55.8±13.5 years. RF was positive in 87%, anti-CCP in 75.6% and 15.4 % presented extra-articular manifestations (nodulosis 8.9%, intersticial lung disease 5.3%, other 1.2%). At the start of the study 149 patients (60.6%) were with TNFi, 79 (32.1%) non-TNFi and 18 (7.3%) with JAKi and non-biologic DMARD (nbDMARDs) were used in 84.1% of cases (methotrexate 71.2%, leflunomide 21.4%, other 7.4%). During the study 176 patients (71.5%) continued with the same treatment and in 70 (28.5%) it was changed at least once. 5 patients discontinued the treatment. At the end of the study, 124 patients (50.4%) were with TNFi, 83 (33.7%) non-TNFi and 34 (13.8%) with JAKi. Severe infection was developed in 17 (6.9%) patients (respiratory 7, se sis 4, urinary 3, cellulitis 2, osteomyelitis 1) among them 2 patients had severe infection and herpes zoster and 3 developed a second infection. 9 patients were with TNFi (52.9%), 6 non- TNFi BT (35.3%) and 2 JAKi (11.8%). Table 1 The inflammatory activity of RA was mild at the time of infection (DAS28: 2.7±1.2). The median time until infection was: TNFi 28.05 months, non- TNFi BT 25.03 and Jakinibs 16.97. The Charlson index, concomitant treatment with glucocorticoids (GCC) (not treatment with nbDMARDs), chronic obstructive pulmonary disease (COPD), diabetes (DM), severe liver disease and moderate-severe renal insufficiency were statistically significantly associated with infection. Table 1 Conclusion: In our study, 6.9% of patients with RA treated with BT or JAKi developed severe infection during 4 years of follow-up. Concomitant GCC therapy and comorbidity increased the risk of presenting this complication. Disclosure of Interests: None declared